Appreciation to peer-reviewers 2022 - Sociedad Peruana de Obstetricia y Ginecología (2023)
The Editorial Committee of The Peruvian Journal of Gynecology and Obstetrics (RPGO) thanks the renowned professionals, researchers and academics who contributed selflessly and promptly in the evaluations of the articles published in RPGO Volume 67 during the year 2022, through peer review.